ANTIOXIDANT ACTIVITY OF PIPER CANINUM AND CYCLOOXYGENASE-2 INHIBITION BY METHOXYLATED FLAVONES - Nadri, Muhammad Helmi; Naser, Mohammed Abu Naser; Zulkifli, Razauden Mohamed; Muhamad, Ida Idayu; Ahmad, Farediah; Wan Salleh, Wan Mohd Nuzul Hakimi; Sirat, Hasnah M. (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: The crude extracts and pure compounds isolated from Piper caninum was studied for their bioactivities. Material and method: The present study was carried out with the following aims: (1) to quantify the total phenolic content and free radical scavenging activities of the crude extracts by Folin-Ciocalteu and 1,1-diphenyl-2-picrylhydrazyl free radical scavenging assay. (2) to determine the cyclooxygenase-2 inhibition activities of selected isolated compounds as assessed by molecular docking and in vitro cyclooxygenase-2 inhibition assay. Results: Methanolic extracts of Piper caninum exhibited the highest total phenolic content and free radical scavenging activities. All the pure compounds possessed significant cyclooxygenase-2 inhibition at physiological concentrations. Conclusion: Based on our findings of the molecular docking and in vitro study, we therefore suggest that Piper caninum methoxylated flavones are potent inhibitors of cyclooxygenase-2 at physiological concentrations.